Recent Trends in Performance Appraisal System in Private and Public Sector Banks In India - Chaudhary, Sonika; Maheshwari, Sachin (Journal of Commerce and Trade, 2010)
This paper deals with the prevailing Performance Appraisal System in Indian Banking Industry. This survey conducted in some public and private sector bank. Today latest mantra as being followed by organizations across the world is- “Pay for the performance”. Banking sector is also paying more attention to performance management system, especially to individual performance. Performance appraisal is an important function of the HR department. Its function is to formulate policies related to assessing the performance of the employees and identifying potential for taking up the higher responsibilities. Performance Appraisal is an ongoing exercise not a “one shot” function which is concerned with developing a potential of the employees in order to provide maximum satisfaction to all the employees. It provides employees with the training and developmental opportunity to perform better, helping them to keep up with the changes at the workplace. Now a days, with increase competition, organizations face many challenges. So, organizations must understand the importance of human resource and constantly focus on improving its performance, which will result in the overall improvement in the organizations performance.